Exuberant Intratracheal Granuloma - Stuart, Emelia; Armaneous, Michael; Bracken, David; Crawford, Kayva; Vahabzadeh-Hagh, Andrew M. (Case Reports in Otolaryngology, 2021)
Background. Upper airway granulomas are commonly encountered benign masses and are a result of pronounced tissue reactivity to localized respiratory mucosal trauma. The mechanism of injury to respiratory epithelium is most commonly iatrogenic and associated with intubation or indwelling tracheostomy. Case Report. A 40-year-old obese female with a history of multiple intubations, poorly controlled diabetes mellitus type II, and history of tracheal stenosis presented with sudden onset respiratory distress requiring intubation at an outside hospital. Direct laryngoscopy revealed a rapidly forming transglottic tissue mass, measuring 5.0 × 2.2 × 0.8 cm. The following case represents an unusual exception to our experience with granulomas given its rapidity of onset and migration of tissue around the endotracheal tube. Discussion. Laryngeal erythema and granulation formation are expected postintubation findings in most patients; however, the large size of granuloma tissue and rapid onset of symptoms in this case make it remarkable. Our patient had multiple risk factors for postintubation stenosis: female sex, poorly controlled diabetes, hypertension, obesity, and multiple prior intubations for periods lasting longer than forty-eight hours. Conclusion. Our case highlights a rare laryngeal finding of a large granulation tissue mass causing sudden onset airway obstruction.